Islamic Counseling Base on Prophetic Values Improve Social Skills: A Systematic Literature Review - Ilham; Sakaruddin Mandjarreki; St. Rahmatiah; Syamraeni (G-Couns: Jurnal Bimbingan dan Konseling, 2026)
Prophetic values can be integrated into Islamic counseling practices to improve social skills. This study aims to examine the relationship between the application of Islamic counseling grounded in prophetic values and improvements in social skills. This study was conducted because there is still limited systematic synthesis regarding the integration of prophetic values in Islamic counseling in the context of social skills development. The principles of benefit, influence, and method were obtained through qualitative research using a systematic literature review (SLR) approach based on PRISMA, with literature searches in five databases (Scopus, Google Scholar, Sinta, Dimensions, and Garuda) from 2013 to 2021. From a rigorous selection process with criteria for including relevant journal articles and excluding non-qualified ones, 15 articles were obtained that were eligible for analysis. The results of the study show a close qualitative relationship between prophetic values and social skills, in which integrating these values affects moral awareness, empathy, effective communication, and the quality of social interactions. heoretically, these findings enrich the prophetic-based Islamic counseling paradigm. In practice, they support school counseling interventions, particularly for students with diverse abilities. uture research includes large-scale RCTs, the development of predictive measurement tools, and comparative studies with conventional counseling. Keywords: human being, Islamic counseling, social skills, prophetic values, systematic literature review